Development Of Chemistry Supplement Book with Ethno-SocioScientific Context on The Sub-Topic of Alcohol to Improve Students'Cognitive Learning Outcomes - Kuki, Agustina Dua; Susanty, Petronela Ivoni; Wata, Rafaelis Stefanya (Universitas Negeri Semarang, 2025)
This study aims to develop a valid, practical, and effective ethno-socioscientific supplementary book on the topic of alcohol to enhance students' cognitive learning outcomes. Employing a Research and Development methodology, the study utilizes the 4D development model, limited here to three stages: Define, Design, and Development. Research instruments included validation sheets, response questionnaires, and effectiveness test sheets. Validation results indicate the book is highly valid, with an average Aiken score of 0.91. The practicality test, involving 27 students, yielded a score of 96%, categorized as very practical. The effectiveness test, based on N-gain results, produced an average score of 0.61, categorized as moderate. The presentation of contextual phenomena in the ethno-SSI supplement book to deepen their understandingof chemistry concepts and broaden their cultural horizons. In conclusion, the ethno-socioscientific Sikka culture chemistry supplement book is valid, practical, and effective in improving students' cognitive learning outcomes on the subtopic of alcohol.